2016
DOI: 10.1111/jhn.12426
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarianism and breast, colorectal and prostate cancer risk: an overview and meta‐analysis of cohort studies

Abstract: A summary of the existing evidence from cohort studies on vegetarian diets showed that complete exclusion of any source of protein from the diet is not associated with further benefits for human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 49 publications
3
65
0
1
Order By: Relevance
“…A similar conclusion was reported in a meta-analysis and systematic review of prospective cohort studies by Godos et al (2017). According to their findings, the risk of colorectal cancer was lower in the population that consumed a semivegetarian diet (relative risk 0.86) and pescovegetarian diet (relative risk 0.67) when compared to non-vegetarians (Godos et al, 2017). However, in contrast to this, Koushik et al (2007) followed 756,217 men and women for 6 to 20 years and showed that excessive intake of fruit and vegetables was not strongly associated with colon cancer risk reduction.…”
Section: Health Benefi Ts Of Vegetarianismsupporting
confidence: 88%
See 2 more Smart Citations
“…A similar conclusion was reported in a meta-analysis and systematic review of prospective cohort studies by Godos et al (2017). According to their findings, the risk of colorectal cancer was lower in the population that consumed a semivegetarian diet (relative risk 0.86) and pescovegetarian diet (relative risk 0.67) when compared to non-vegetarians (Godos et al, 2017). However, in contrast to this, Koushik et al (2007) followed 756,217 men and women for 6 to 20 years and showed that excessive intake of fruit and vegetables was not strongly associated with colon cancer risk reduction.…”
Section: Health Benefi Ts Of Vegetarianismsupporting
confidence: 88%
“…Furthermore, the authors emphasised that eating a pescovegetarian diet was associated with the lowest risk of colorectal cancer (a 43% risk reduction compared with omnivores), while the risk of colorectal cancer in semivegetarians (risk reduction of 8%) was closest to the risk that meat consumers face (Michelle et al, 2015). A similar conclusion was reported in a meta-analysis and systematic review of prospective cohort studies by Godos et al (2017). According to their findings, the risk of colorectal cancer was lower in the population that consumed a semivegetarian diet (relative risk 0.86) and pescovegetarian diet (relative risk 0.67) when compared to non-vegetarians (Godos et al, 2017).…”
Section: Health Benefi Ts Of Vegetarianismsupporting
confidence: 80%
See 1 more Smart Citation
“…[4][5][6][7] Hence, vegetarian diets or low meat diets may be expected to be associated with a lower risk of CRC given their lack of, or reduced, meat content, but current scientific evidence remains inconsistent and requires further explanation. Some of the inconsistency in findings may be owing to the complete exclusion of any source of meat or fish protein from the diet (pure vegetarian diet) 8 and CRC subsites. 9 Early results from the EPIC-Oxford study found an approximately 50% greater risk of CRC for vegetarians.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that based on the inclusion criteria, no studies on the association between conformance with a vegetarian dietary pattern and health outcomes were identified. Among the studies that evaluated the health effects of vegetarian diets, [28][29][30] the definition of conformance was based largely on what was not consumed, and therefore the comparison in these studies was between selfidentified vegetarians and a control group of nonvegetarians, making it difficult to know what dietary components were consumed and therefore directly associated with any observed health outcomes. Further, the definition of vegetarian varied greatly, with some identified as "pure," "semi," "pesco," and "vegan."…”
Section: Research Snapshotmentioning
confidence: 99%